Molecular chaperone effects on recombinant yield and binding characteristics of an ABA-specific scFv in Escherichia coli - Chen, Shimiao; Shan, Bin; Luo, Yican; Mo, Ganhui; Rasheed, Usman; Lv, Lilan; Yang, Xinyu; Lu, Qinyu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionRecombinant single‐chain variable fragments (scFvs) are promising antibody formats for cost‐effective and scalable production. However, their soluble expression in Escherichia coli is often limited by misfolding and aggregation, particularly for scFvs targeting small molecule haptens such as abscisic acid (ABA). To address this bottleneck, molecular chaperones can be co‐expressed to enhance folding efficiency and functional yield.MethodsAn ABA‐specific scFv was expressed in E. coli BL21(DE3) using five different chaperone plasmids (pG‐KJE8, pGro7, pKJE7, pG-Tf2, and pTf16). Soluble expression was quantified by His‐tag ELISA, and protein identity was confirmed by SDS‐PAGE and Western blot. Functional characterization included competitive ELISA for IC50 and specificity, while secondary structure was analyzed by FT‐IR and circular dichroism spectroscopy.ResultsTrigger Factor (pTf16) significantly improved soluble scFv yield (19.65%) compared to the control (14.20%). The pKJE7 system achieved the highest sensitivity with the lowest IC50, whereas the pTf16 system provided superior specificity and a broader detection range by minimizing cross‐reactivity. Structural analysis revealed that pKJE7‐assisted scFv closely matched the predicted β‐sheet content, correlating with high sensitivity, while pTf16‐assisted scFv avoided non-native α-helices, supporting enhanced specificity. Circular dichroism further demonstrated that pKJE7‐ and pTf16‐assisted scFvs exhibited conformational rigidity consistent with a lock-and-key binding mechanism.DiscussionThis study highlights that molecular chaperone choice influences both structural fidelity and functional performance of ABA‐scFv in E. coli. While pKJE7 favors high sensitivity, pTf16 yields highly specific and structurally stable antibodies. These findings establish a practical basis for developing low‐cost ABA immunoassays with tailored performance for agricultural biotechnology.